483 Effects of Standardized Ileal Digestible Lysine on 7-15 Kg Nursery Pigs Growth Performance. (10th April 2018) - Nichols, G E; Vier, C M; Lerner, A B; Menegat, M B; Cemin, H S; Jones, C K; DeRouchey, J M; Tokach, M D; Goodband, B D; Woodworth, J C; Dritz, S S
Abstract: A total of 300 pigs (DNA 241 × 600; initial pen average BW of 6.98 ± 0.12 kg) were used in a 22 d growth trial to determine the standardized ileal digestible (SID) Lys requirement of nursery pigs from 7 to 15 kg. Pigs were weaned at approximately 21 d of age and allotted to pens based on BW and gender. There were 10 replicate pens per treatment and 6 pigs per pen. Pigs were fed a common diet for 10 d post-weaning. Pens were then randomly assigned to 1 of 6 experimental diets in a randomized complete block design based on BW. The 6 dietary treatments were formulated to 1.10, 1.20, 1.30, 1.40, 1.50, and 1.60% SID Lys by increasing the inclusion of crystalline amino acids at the expense of corn. Experimental diets were fed for 11 d. Data were analyzed using generalized linear and non-linear mixed models, fitting the data with heterogeneous residual variances as needed. Competing models included linear (LM), quadratic polynomial (QP), broken-line linear, and broken-line quadratic. For the overall treatment period, increasing SID Lys linearly improved ( P <0.001) ADG and G:F, with no evidence for differences observed in ADFI ( P> 0.05). For ADG, the best-fitting models were LM [predicted equation: 239.95 + 124.74 × (SID Lys)] and QP [predicted equation: -321.14 + 975.22 × (SID Lys) – 315.70 × (SID Lys) 2 ]. The maximum ADG was estimated at 1.54% (95% CI: [1.34, >1.60]%), with 99% of the maximum ADG achieved at 1.43% SID Lys in the QP model. Similarly, the best-fitting models for feed efficiency were the QP [predicted equation: 89.81 + 261.27 × (SID Lys) – 63.50 × (SID Lys) 2 ] and the LM [predicted equation: 222.26 + 86.18 × (SID Lys)], estimating the requirement at greater than 1.60% for both models. In conclusion, the mean SID Lys required for nursery pigs from 7 to 15 kg ranged from 1.54% to at least 1.60% depending on the model and response criteria considered.